VD_FINDINFO HC / 2012 / 14 vom 24. Oktober 2011 - VD Tribunal cantonal (2011)
BAIL À LOYER, LOGEMENT SOCIAL, FRAIS ACCESSOIRES | 253b al. 3 CO, 269d al. 3 CO, 308 al. 2 CPC (CH), 312 al. 1 CPC (CH), 334 al. 1 CPC (CH)